The Relevance Of Logical Principles As The Basis For Scientific Thinking In The Development Of Management Science: A Systematic Study - Hilwa Rohmahdiniyah Nur Azizah; Trivena Gilang Permatasari; Agung Winarno; Subagyo (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the role of logic in the development of management science and managerial decision-making. This study uses a qualitative research method with a literature review approach. The research population includes scientific articles, books, and academic publications that discuss the topics of logic, management theory, and decision-making. The research sample was selected purposively based on criteria of relevance, accessibility, and thematic suitability, resulting in a number of literature sources that were analyzed in depth. The research instrument was a literature analysis sheet used to assess the suitability of concepts, clarity of argumentation, and theoretical contributions of each source. The results of the study show that logic plays an important role as the basis of scientific reasoning in constructing management theory, helping to formulate consistent propositions, and supporting a systematic and unbiased decision-making process. Logic has been proven to strengthen the accuracy of problem formulation, consistency of argumentation, and objectivity of analysis in both research and managerial practice. Thus, logic not only functions as a philosophical concept but is also an essential instrument for improving the quality of scientific studies and the effectiveness of decisions in management.